TESTING OF POLONITE, GAZOBETON, PAREPARE BLACK VOLCANIC SAND BEACH, AND KADIDIRI CORAL BEACH SAND FOR PHOSPHORUS REMOVAL FROM WATER AND WASTEWATER IN CONSTRUCTED WETLAND - Dian Dwi Kartikasari; Supranto -; Rochmadi - (ASEAN Journal of Systems Engineering, 2013)
Characteristics of domestic wastewater in Indonesia generally contain phosphorus 4-15 mg/L. Phosphorus in wastewater must be treated to reduce the phosphorus content according to the Indonesia: Government Regulation No. 82/2001 management of water quality and control over water pollution, maximum allowable levels is 0.2 mg/L. A 1953 report from the Max Planck Institute in Germany by Dr. Kathe Seidal discusses the possibility of using wetland plants to remove nutrients from wastewater. The objectives of this research are to ascertain whether Polonite, Gazobeton, Parepare black volcanic sand beach and Kadidiri coral beach sand can be used as sorbent materials and to obtain the data of phosphorus sorption capacity, efficiency and phosphorus adsorption capacity constant of those materials. This research consists of batch and box experiment. Batch experiment was conducted for all material by mechanically shaking sample for several minutes with varying concentrations of the artificial phosphorus solution prepared from KH2PO4 and wastewater. Box experiment was conducted to evaluate the phosphorus removal by Gazobeton in long term experiment. The highest sorption capacity was attained by polonite 0.917 g/Kg, was followed by gazobeton 0.504 g/Kg, Parepare black volcanic sand beach 0.174 g/Kg and then the finally Kadidiri coral beach sand 0.131 g/Kg. The phosphorus sorption efficiency by Polonite, Gazobeton, Parepare black volcanic sand beach and Kadidiri coral beach sand each Kg are 91%, 50%; 17% and 13% respectively. Phosphorus adsorption capacity constant of polonite is 4906 L/g gazobeton is 115 L/g Parepare black volcanic sand beach is 19 L/g and Kadidiri coral beach sand is 14 L/g